Influence of soluble oil-based TiO2 nanofluid on heat transfer performance of cutting fluid. (August 2017) - Salimi-Yasar, Hamid; Zeinali Heris, Saeed; Shanbedi, Mehdi
Abstract: Herein, the effects of various parameters on heat transfer performance and temperature distribution during a drilling operation have been investigated experimentally to find favorable conditions in the drilling processes. Three modes of dry drilling, drilling with pure cutting fluid and soluble oil-based TiO2 nanofluid were employed. The average heat transfer ratio showed an upward trend with increasing of Reynolds number, increasing from 5.7% at Re of 300 to 9.5% at Re of 900 at the constant weight concentration of 0.03%. As a promising result, temperature distribution declined in drilling procedure in the presence of nanofluid as compared to the dry drilling as well as drilling with cutting fluid. So, soluble oil-based TiO2 nanofluid can be a great alternative for drilling procedure. Graphical abstract: Highlights: Tool's service life decreased in dry drilling compared to nano TiO2 based nanofluid. Nanoparticles are effective in improving heat transfer properties of cutting fluids. Soluble oil/TiO2 Cutting nanofluid cause less amortization. The soluble oil/TiO2 nanofluid decreases the temperature of tool and the workpiece. Soluble oil/TiO2 nanofluid produced less erosion &drill attrition than dry drilling.